Thermo-mechanical coupled problems at finite strains - Vaz M.* (2008)
This paper discusses some thermodynamic aspects in association with a large strain/large displacement elastic-plastic formulation aiming at application to metal forming problems. The mechanical solution adopts the multiplicative decomposition of the gradient of deformation into elastic, plastic and thermal components. The approach is illustrated by analysing the thermal effects in the plastic deformation of low-carbon steel specimens subject to tensile loading.